Genetic variation of MMP‐2(‐735 C>T) and MMP‐9(‐1562 C>T) gene in risk of development of HAND and severity of HAND. (September 2016) - Singh, HariOm; Marathe, Shruti D.; Nema, Vijay; Ghate, Manisha V.; Gangakhedkar, Raman R.
Abstract: Background: Astrocytes are susceptible to HIV‐1 infection. Neurocognitive dysfunction has also been associated with the toxicity of certain antiretroviral drugs. HIV‐1 induced neurological toxicity has been associated with deficiency of matrix metalloproteinases. Therefore, we evaluated the association of MMP‐2 (−735C > T) and MMP‐9 (−1562C > T) polymorphisms with respect to the susceptibility of developing HIV‐associated neurocognitive disorders (HAND) and its severity. Methods: We enrolled 50 HIV‐infected individuals with HAND, 130 without HAND and 150 unrelated healthy controls. Polymorphism for MMP‐2 ‐735C > T and MMP‐9 ‐1562C > T genes was genotyped by polymerase chain reaction‐restriction fragment length polymorphism. Results: Individuals with the MMP‐ 2 ‐735 CT genotype and ‐735 T allele were at higher risk of developing HAND [odds ratio (OR) = 5.27, 95% confidence interval (CI) = 1.30–21.35, p  = 0.02 and OR = 2.27, 95% CI = 1.57–3.27, p  = 0.0001 respectively]. The MMP‐ 2 ‐735 CT genotype and −735 T allele of MMP‐ 2 were associated with a reduced likelihood of severe HAND (OR =0.32, 95% CI = 0.15–0.66, p  = 0.002 and OR = 0.32, 95% CI = 0.14–0.71, p  = 0.005). When evaluating gene–gene interaction models, the combined genotype MMP‐2 ‐735TT +  MMP‐9 ‐1562CC and MMP‐2 ‐735CT +  MMP‐9 ‐1562CT was associated with the risk of developing HAND (OR = 4.84, p  = 0.0001, OR = 1.81, p  = 0.03). However, individuals with the combined genotype of MMP‐2 ‐735TT +  MMP‐9 ‐1562CC were found to be protective for severe HAND (OR = 0.30, 95% CI = 0.13–0.67, p  = 0.003). Conclusions: Individuals with the MMP‐2 ‐735CT genotype, −735 T allele and combined genotype MMP‐2 ‐ 735TT +  MMP‐9 ‐1562CC had an enhanced risk of developing HAND. Those with the MMP‐ 2 ‐735 CT genotype, −735 T allele and combined genotype of MMP‐2 ‐735TT +  MMP‐9 ‐1562CC were suggested to have protection from developing severe HAND.